Copy number variation, chromosome rearrangement, and their association with recombination during avian evolution - Völker, Martin; Backström, Niclas; Skinner, Benjamin M.; Langley, Elizabeth J.; Bunzey, Sydney K.; Ellegren, Hans; Griffin, Darren K. (Genome Research, 2010)
Chromosomal rearrangements and copy number variants (CNVs) play key roles in genome evolution and genetic disease; however, the molecular mechanisms underlying these types of structural genomic variation are not fully understood. The availability of complete genome sequences for two bird species, the chicken and the zebra finch, provides, for the first time, an ideal opportunity to analyze the relationship between structural genomic variation (chromosomal and CNV) and recombination on a genome-wide level. The aims of this study were therefore threefold: (1) to combine bioinformatics, physical mapping to produce comprehensive comparative maps of the genomes of chicken and zebra finch. In so doing, this allowed the identification of evolutionary chromosomal rearrangements distinguishing them. The previously reported interchromosomal conservation of synteny was confirmed, but a larger than expected number of intrachromosomal rearrangements were reported; (2) to hybridize zebra finch genomic DNA to a chicken tiling path microarray and identify CNVs in the zebra finch genome relative to chicken; 32 interspecific CNVs were identified; and (3) to test the hypothesis that there is an association between CNV, chromosomal rearrangements, and recombination by correlating data from (1) and (2) with recombination rate data from a high-resolution genetic linkage map of the zebra finch. We found a highly significant association of both chromosomal rearrangements and CNVs with elevated recombination rates. The results thus provide support for the notion of recombination-based processes playing a major role in avian genome evolution.
10.1101/gr.103663.109